The Impacts of Introduction of VAT On the Audit Profession and Economy in The UAE: Auditors' Perspective - Aisha Saderuddin; Yasser Barghathi (Journal of Accounting and Management Information Systems (JAMIS), 2018)
Commencing 1st January 2018, Value Added Tax (VAT) was made effective in the UAE. The decision was made in light of the fall in oil prices and with the aim of diversifying the country's revenue to non-hydrocarbon sectors. This paper examines the impacts of introducing VAT on the audit profession and the economy in the UAE. Unlike previous studies which have viewed this topic from a business or consumer perspective, this paper examines it from an auditor's perspective. Given that this topic relates to a new policy and there isn't much literature available on it, this study explores the auditors' perceptions about the implications of this new policy on both; audit profession and the economy. This paper employs semi-structured interviews with auditors from both Big-Four as well as Non-Big-Four audit firms in order to collect data. This research, apart from being a timely and trending topic, may be useful to academicians, tax specialists, auditors, businesses and regulatory bodies. The findings of the study suggest that auditors are optimistic about VAT implementation in the UAE with respect to the growth in the economy in the long run. However, they have mixed perceptions regarding the audit profession and believe that there is no material impact on it due to VAT implementation.
Keywords: M41; 650; VAT; auditors; UAE; perceptions; economy; qualitative; Big 4 and non-Big 4